2018
DOI: 10.1103/physreva.98.043418
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field polarizability-enhanced dissociative ionization

Abstract: We investigate dissociative single and double ionization of HeH + induced by intense femtosecond laser pulses. By employing a semi-classical model with nuclear trajectories moving on field-dressed surfaces and ionization events treated as stochastical jumps, we identify a strong-field mechanism wherein the molecules dynamically align along the laser polarization axis and stretch towards a critical internuclear distance before getting dissociative ionized. As the tunnel-ionization rate is greater for larger int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Although the asymmetry amplitude slightly decreases compared to the main peak in the OC + + S + channel, which we attribute to the effects of molecular rotation due to a higher potential barrier along the O-C bond breaking. This result indicates that the orientation of the parent OCS 2+ ions is mainly determined by the ionization step, even for different dissociation channels as discussed in the previous studies of polar molecules (Ohmura and Tachiya, 2008;Holmegaard et al, 2010;Dimitrovski et al, 2011;Li et al, 2011;Wu et al, 2012;Ohmura et al, 2014;Li et al, 2016;Wustelt et al, 2018;Yue et al, 2018;Endo et al, 2019;Ohmura et al, 2019).…”
Section: The Minor Dissociation Channel: C-o Bond Breakingsupporting
confidence: 58%
See 1 more Smart Citation
“…Although the asymmetry amplitude slightly decreases compared to the main peak in the OC + + S + channel, which we attribute to the effects of molecular rotation due to a higher potential barrier along the O-C bond breaking. This result indicates that the orientation of the parent OCS 2+ ions is mainly determined by the ionization step, even for different dissociation channels as discussed in the previous studies of polar molecules (Ohmura and Tachiya, 2008;Holmegaard et al, 2010;Dimitrovski et al, 2011;Li et al, 2011;Wu et al, 2012;Ohmura et al, 2014;Li et al, 2016;Wustelt et al, 2018;Yue et al, 2018;Endo et al, 2019;Ohmura et al, 2019).…”
Section: The Minor Dissociation Channel: C-o Bond Breakingsupporting
confidence: 58%
“…In the case of polar (asymmetric) molecules on the contrary, the fragment ejection direction in asymmetric laser fields has been exclusively explained by the anisotropy of the tunneling ionization rate, which is determined by the shape of the ionizing molecular orbital (usually the highest occupied molecular orbital, HOMO) and the molecule's permanent dipole moment (Ohmura and Tachiya, 2008;Holmegaard et al, 2010;Dimitrovski et al, 2011;Li et al, 2011;Wu et al, 2012;Ohmura et al, 2014;Li et al, 2016;Wustelt et al, 2018;Yue et al, 2018;Endo et al, 2019;Ohmura et al, 2019), rather than by post-ionization interactions. Although post-ionization interactions should be important even for the dissociation of polar molecules, their contributions are generally buried under the strong anisotropy of the tunneling ionization rate.…”
Section: Introductionmentioning
confidence: 99%
“…1(b), results only in Q2 and Q4 show large amplitudes. It has been shown that vibrating HeH + stretches rapidly towards larger internuclear distances R due to vibration excitation [6,29,30]. For the present cases, with calculating R-dependent ionization probability as in [29], our analyses show that the main contributions to ionization occur around R = 2 a.u.…”
Section: Cases Of Heh +mentioning
confidence: 49%
“…It should be stressed that in this paper, we focus our discussions on atoms. For molecules with multi-center structure, some complex effects emerge in strong-field ionization, such as quantum interference between the molecular centers during tunneling [53][54][55], permanent dipole induced large Stark effect [56][57][58], laser induced nuclear quick stretching [59][60][61][62][63], and permanent dipole induced direct vibration excitation [64][65][66], etc.. For the purpose of achieving more precise control and measurement of the electron motion within the molecule with 2D laser fields, studies on influences of molecular structure and structure-related effects on properties of 2D tunneling are also expected.…”
Section: Extended Discussionmentioning
confidence: 99%